Copy Number Status of TERT Gene in a Myeloid Leukaemia Cell Line, K562: Application of Interphase Fluorescence in situ Hybridization (FISH) Analysis - Ahmad Syibli, Othman; Nor Atifah, Mohd Adam; Ravindran, Ankathil; Rosline, Hassan (2011)
Telomeraseisribonucleoproteinenzymecomplexconsistingoftwomaincorecomponents;reversetranscriptase(TERT),andRNAtemplatefortelomericDNAsynthesis(TERC).TERTgeneactsascatalyticcomponentinthisenzymeandislocatedonchromosome5p15.IthasbeenreportedthatthereisanamplificationorincreaseofTERTgenecopynumberinhumancancercelllinesandprimarytumoursampleswhichmayassociatewithincreasedtelomeraseactivity.Inourstudy,dual-colorassayprobewasusedinfluorescencein situhybridization(FISH)analysisthatcoveredthegenomicregionencodingTERT(Redsignal)togetherwithaspecificsequenceofEGR1(Greensignal)at5q31tofacilitatechromosomeidentification.Innormalcells,theFISHsignalpatternwasobservedastwogreensignalsandtworedsignals(2G2R).AmplificationoftheTERTgenehasbeendetectedinmorethan90%ofthecellsincelllineintheleukaemia.Besidesthat,aneusomyofchromosome5wasalsodetectedindicatingthepresenceofthreecopiesofchromosome5with3G3Rsignalpattern.Thus,theapplicationofinterphaseFISHtechniquefordetectionofTERTgeneamplificationhasbeensuccessfullyoptimized